CREATIVE APPROACH TO THE FORMATION OF STUDENTS' SPIRITUAL COMPETENCE IN THE PEDAGOGICAL PROCESS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The article analyzes the importance of creative approach in the formation of students' spiritual competence in the educational process. It describes the role of creative methods in the development of personal values and moral values.